Prognostic impact of CD8-positive tumour-infiltrating lymphocytes and PD-L1 expression in salivary gland cancer. (December 2020) - Kesar, Nikolina; Winkelmann, Ria; Oppermann, Julius; Ghanaati, Shahram; Martin, Daniel; Neumayer, Thomas; Balster, Sven; Rödel, Claus; Rödel, Franz; von der Grün, Jens; Balermpas, Panagiotis
Highlights: CD8 + TILs correlate with impaired outcome in head and neck salivary gland carcinoma. Simultaneous negative impact of PD-L1 and PD-1 expression advocates TILs exhaustion. Immunogenicity in salivary gland cancer depends on the histopathological subtype. Adenoid cystic carcinoma might demonstrate immunological ignorance. Abstract: Objectives: Aim of the study was to evaluate the prognostic impact of CD8-positive (CD8 + ) tumour-infiltrating lymphocytes (TILs) and PD-L1 expression on the outcome of patients with malignant salivary gland neoplasms. Materials and methods: Formalin-fixed, paraffin-embedded tissue samples and clinicopathological data from patients treated for salivary gland carcinoma in a head and neck cancer centre were retrospectively retrieved. Immunohistochemical staining was applied on sections of 84 specimens of 12 different histological subtypes. Both CD8 and PD-L1 expression were rated by semi-automated cell counts by a digital image analysis programme. Survival analyses were performed by the log-rank test on the univariate level, and the Cox model was applied on the multivariate level. Associations between immunological markers and clinicopathological variables were estimated by the Pearson chi-squared test. Additionally, PD-1 was estimated as an exhaustion marker of CD8 + TILs. Results: Patients exceeding a tumour proportion score ≥5% regarding PD-L1 expression demonstrated a significantly decreased survival, as did individuals with an overall high CD8 + cell density. Particularly, high CD8 + cell counts in the invasive front of the respective tumour tissue significantly coincided with a poor outcome. Also, high numbers of CD8 + TILs significantly matched with a high quantity of PD-1 + TILs. Conclusion: CD8 + TILs abundance in the peritumoural microenvironment correlates with impaired outcome of patients with salivary gland carcinoma. The simultaneous negative prognostic impact of PD-L1 expression and presence of PD-1 + TILs advocates an immune checkpoint-controlled mechanism of CD8 + TILs exhaustion for these tumours and paves the way for future treatment strategies.